Addressing Environmental Challenges of Porphyrin Mixtures Obtained from Statistical Syntheses - Hölzel, Helen; Muth, Maximilian; Lungerich, Dominik; Jux, Norbert (Chemistry Methods, 2021)
Syntheses of complex molecular mixtures on the preparative scale are often challenging steps for chemists, which go hand in hand with expensive purification steps. Herein, the preparation and isolation of unsymmetrically substituted porphyrins, obtained from statistical reactions between two benzaldehydes, were investigated. Therefore, a semi-automated modular process was developed to lower the consumable costs, save time, and reduce waste production. We utilized a monomode microwave reactor equipped with an autosampler, and a medium pressure liquid chromatography (MPLC) flash purification device, equipped with a UV/Vis detector and a re-usable glass column packed with SiO2. With this method, it was possible to synthesize and purify several statistical porphyrin mixtures, while simultaneously reducing the environmental factor (E-factor) significantly, compared to conventionally performed porphyrin syntheses. Our approach shows that a sustainable investigation of academically relevant low-symmetrical porphyrins can be carried out feasibly, without sacrificing invested time.
CRIS-Team Scopus Importer:2024-12-16
Keywords: chromatography; E-factor; Porphyrin; statistical synthesis; sustainability

Adsorption Behavior of a Cyano-Functionalized Porphyrin on Cu(111) and Ag(111): From Molecular Wires to Ordered Supramolecular Two-Dimensional Aggregates - Lepper, Michael; Schmitt, Tobias; Gurrath, Martin; Raschmann, Marco; Zhang, Liang; Stark, Michael Werner; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Schneider, M. Alexander; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2017)
We investigate the impact of peripheral cyano functionalization of the previously well-studied 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy (STM) and density functional theory (DFT). The adsorption behavior of 2H-tetralds(p-cyano)-phenylporphyrin (2HTCNPP) is studied at room temperature and at 80 K on Cu(111) and Ag(111). Interestingly, the cyano-functionalized porphyrins tend to form isolated ID chains on Cu(111), in particular after mild annealing at 350 K. The individual 2HTCNPPs as well as the formed chains are oriented along the main crystallographic directions of the Cu(111) substrate due to a strongly attractive and site-specific interaction between the iminic nitrogens of the 2HTCNPP and Cu substrate atoms. The linking within the 1D molecular chains is realized by Cu adatoms as evidenced by comparison of STM and DFT. In contrast, on Ag(111) the molecules assemble into 2D supramolecular layers with long-range order and a square unit cell, stabilized by molecule-molecule interactions. The orientation of the molecules with respect to the unit cell lattice vectors leads to organizational chirality. By codeposition of cobalt, the porphyrin molecules are metalated at room temperature. We did not observe any evidence for metal-organic network formation on Ag(111), even after varying the deposition parameters or the order of metal and porphyrin deposition. Our study shows that cyano functionalization of porphyrins can give rise to novel and unique self-assembled structures like 1D molecular chains without any cross-connections via adatom linking.

Controlling the Self-Metalation Rate of Tetraphenylporphyrins on Cu(111) via Cyano Functionalization - Lepper, Michael; Köbl, Julia; Zhang, Liang; Meusel, Manuel; Hölzel, Helen; Lungerich, Dominik; Jux, Norbert; De Siervo, Abner; Meyer, Bernd; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2018)
The reaction rate of the self-metalation of free-base tetraphenylporphyrins (TPPs) on Cu(111) increases with the number of cyano groups (n=0, 1, 2, 4) attached at the para positions of the phenyl rings. The findings are based on isothermal scanning tunneling microscopy (STM) measurements. At room temperature, all investigated free-base TPP derivatives adsorb as individual molecules and are aligned with respect to densely packed Cu substrate rows. Annealing at 400K leads to the formation of linear dimers and/or multimers via CN-Cu-CN bonds, accompanied by self-metalation of the free-base porphyrins following a first-order rate equation. When comparing the non-cyano-functionalized and the tetracyano-functionalized molecules, we find a decrease of the reaction rate by a factor of more than 20, corresponding to an increase of the activation energy from 1.48 to 1.59eV. Density functional theory (DFT) calculations give insights into the influence of the peripheral electron-withdrawing cyano groups and explain the experimentally observed effects.
Keywords: cyano functionalization; porphyrinoids; scanning tunneling microscopy; self-metalation; surface chemistry

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

Metalation and coordination reactions of 2H-meso-trans-di(p-cyanophenyl) porphyrin on Ag(111) with coadsorbed cobalt atoms - Kuliga, Jan; Zhang, Liang; Lepper, Michael; Lungerich, Dominik; Hölzel, Helen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2018)
We investigated the metalation and coordination reactions of Co with 2H-5,15-bis(para-cyanophenyl)10,20-bisphenylporphyrin (2HtransDCNPP) on a Ag(111) surface by scanning tunneling microscopy. At room temperature (RT), 2HtransDCNPPs self-assemble into a supramolecular structure stabilized by intermolecular hydrogen bonding. The metalation of 2HtransDCNPP is achieved either by depositing Co atoms onto the supramolecular structure at RT, or, alternatively, by depositing the molecules onto a submonolayer Co-precovered Ag(111) surface with a subsequent heating to 500 K. In addition, the molecules coordinate to Co atoms through the N atoms in the peripheral cyano groups with a preference of isolated 4-fold coordination motifs at RT.

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan; De Campos Ferreirra, Rodrigo Cezar; Adhikari, Rajan; Massicot, Stephen; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Marbach, Hubertus; De Siervo, Abner; Steinrück, Hans-Peter (ChemPhysChem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20-terakis(4-cyanophenyl)porphyrin (2HTCNPP) with post-deposited Zn atoms and the targeted reaction product Zn-5,10,15,20-terakis(4-cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post-deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post-deposited Zn. We attribute this to metastable SAT ("sitting atop") complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.
CRIS-Team WoS Importer:2021-01-29

Screening Supramolecular Interactions between Carbon Nanodots and Porphyrins - Cadranel, Alejandro; Strauß, Volker; Margraf, Johannes; Winterfeld, Kim; Vogl, Christoph; Dordevic, Luka; Arcudi, Francesca; Hölzel, Helen; Jux, Norbert; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
We present an in-depth investigation regarding the electron-accepting nature of pressure-synthesized carbon nanodots (pCNDs) in combination with porphyrins as excited-state electron donors. To this end, electrostatic attractions involving negative charges, which are present on the pCND surface, are essential to govern the hybrid assembly, on one hand, and charge separation, on the other hand.
CRIS-Team Scopus Importer:2022-04-14

Time-resolved imaging and analysis of the electron beam-induced formation of an open-cage metallo-azafullerene - Hölzel, Helen; Lee, Sol; Amsharov, Konstantin Yu; Jux, Norbert; Harano, Koji; Nakamura, Eiichi; Lungerich, Dominik (Nature Chemistry, 2023)
The visualization of single-molecule reactions provides crucial insights into chemical processes, and the ability to do so has grown with the advances in high-resolution transmission electron microscopy. There is currently a limited mechanistic understanding of chemical reactions under the electron beam. However, such reactions may enable synthetic methodologies that cannot be accessed by traditional organic chemistry methods. Here we demonstrate the synthetic use of the electron beam, by in-depth single-molecule, atomic-resolution, time-resolved transmission electron microscopy studies, in inducing the formation of a doubly holed fullerene-porphyrin cage structure from a well-defined benzoporphyrin precursor deposited on graphene. Through real-time imaging, we analyse the hybrid’s ability to host up to two Pb atoms, and subsequently probe the dynamics of the Pb–Pb binding motif in this exotic metallo-organic cage structure. Through simulation, we conclude that the secondary electrons, which accumulate in the periphery of the irradiated area, can also initiate chemical reactions. Consequently, designing advanced carbon nanostructures by electron-beam lithography will depend on the understanding and limitations of molecular radiation chemistry. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-09-29